2020 Physics Education Research Conference Proceedings 2020
DOI: 10.1119/perc.2020.pr.guthrie
|View full text |Cite
|
Sign up to set email alerts
|

A tale of two guessing strategies: interpreting the time students spend solving problems through online log data

Abstract: Interpretation of student behavior in online learning platforms based on log data is complicated by not being able to directly observe the learner. In this paper, we attempt to identify data patterns that signal either guessing on assessment problems or disengaging from the task for students while working through homework modules in an introductory physics class by contrasting data from the general student population with those who completed homework modules in controlled, observed environments. We found that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…In two earlier studies on OLMs 15,20 , those types of engaged behaviors are observed to be more frequently observed among higher performing students. Behaivor (a) was indicative of higher incoming knowledge, whereas behavior (b) was often associated with students who needs to learn the material, and more often observed on harder modules.…”
Section: Engaged Modulesmentioning
confidence: 78%
“…In two earlier studies on OLMs 15,20 , those types of engaged behaviors are observed to be more frequently observed among higher performing students. Behaivor (a) was indicative of higher incoming knowledge, whereas behavior (b) was often associated with students who needs to learn the material, and more often observed on harder modules.…”
Section: Engaged Modulesmentioning
confidence: 78%
“…In the current study, we fit the log duration of each assessment attempt using either normal or skewed distribution models using the R package mixsmsn ( Prates and Cabral, 2009 ), following the fitting procedure described in detail in the appendix of a previous study ( Chen et al, 2020 ). In the case when a single component distributed was the best fit for the duration, the cutoff was set as either 2 standard deviations below the mean duration, or 15 s, whichever was longer ( Guthrie et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…The mandatory first AC attempt on each OLM requires students to plan on whether to engage with the problems or randomly submit a response without reading and proceeding to the IC. Previous studies [6,12] suggest that attempts submitted under 15 seconds are likely generated by students who skipped reading the problems in the AC, whereas attempts between 15 and 35 seconds are likely generated by students who read the problems but didn't know how to solve them properly. Attempts longer than 35 seconds have a higher probability of being a genuine attempt at solving the AC problems and are more frequently observed among high performing students.…”
Section: Sequencementioning
confidence: 99%